Makna Simbolik dalam Legenda Minangkabau “Malin Kundang” - Nazwah Alisca SK; Nina Queena Hadi Putri (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
The legend of Malin Kundang is one of the most well-known folktales in West Sumatra, rich with moral messages and cultural symbolism. This study aims to explore the symbolic meanings embedded within the narrative elements of the Malin Kundang story, including characters, plot, setting, and events. The research applies a qualitative descriptive approach with semiotic analysis. The findings reveal that the character of Malin Kundang symbolizes a disobedient child who violates the customary norms of the Minangkabau culture, while the mother’s curse and the transformation into stone represent the consequences of neglecting cultural values and local wisdom. This legend functions not only as entertainment but also as a medium for the internalization of moral values and traditional teachings within Minangkabau society.